Study on the Characteristics of Traction Forces Difference Asymmetric Steering Bogies - Yan Shi; Junxiong Hu; Weihua Ma (Shock and Vibration)
This article comes up with a new concept of applying the difference between traction forces on front and rear wheelsets to guiding control, as well as the design of a new type of structurally simple asymmetrical radial bogies, which lead to the proposition of traction forces difference-steering asymmetric radial bogies. The traction forces difference-steering asymmetric radial bogies are referred to as TFDA-bogies, in which the difference of longitudinal creep forces between front and rear wheels produces radial steering of both wheelsets. The concept of traction difference is incorporated into guiding control and bogie structure is also simplified in the form of asymmetrical radial bogies. Angle sensors are mounted to facilitate the change of electric currents of the front and rear traction motors to control the guiding mechanism so that wheelsets can adopt the radial position. With SIMPACK, the multibody dynamics analysis software, three whole vehicle models of TFDA-bogies, radial bogies, and conventional bogies are set up and comparative analyses are made on the lead wheel angle of attack, lead wheel lateral force, lead wheel friction power, and total vehicle friction power under idle running condition and traction condition, respectively. Results show that TFDA-bogies are radial bogies with simplified structure.